Synthesis and luminescence of graphene-nano calcium sulphide composite - Sharma, Geeta; Patil, K. R.; Gosavi, S. W. (Materials Chemistry and Physics, 2014)
Graphene-nanocrystalline calcium sulphide has been synthesized using in-situ reduction of calcium salt and graphene oxide. Graphene oxide was prepared using Hummer's method. Surface morphology and crystal structure of samples were observed by transmission electron microscopy (TEM) and X-Ray diffraction (XRD). Ultra thin graphene and graphene oxide sheets with size ranging between tens to several hundreds of square nanometers are observed in TEM images. The TEM micrographs of G-CaS show that CaS particles are embedded in graphene sheets and the average particle size of CaS particles in the composite is less than 50 nm. The reduction in the intensity of various functional groups in FTIR spectrum also confirms the formation of graphene. The UV-Visible spectra of CaS shows absorption peak at 220 nm with a small shoulder at 250 nm whereas in G-CaS 220 nm absorption peak has reduced intensity and the shoulder at 250 nm has now shifted to 270 nm due to modification in the defect structure of CaS by graphene. CaS and G-CaS shows photoluminescence emission at 470 nm (lambda(exc.) = 375 nm) and 440 nm (lambda(exc.) = 350 nm) respectively, however emission intensity of G-CaS is relatively lower than CaS. Although the emission intensity is found to be lower than CaS, addition of CaS to graphene in G-CaS complex has made graphene luminescent. XPS spectra also indicate reduction of various oxygen containing functional groups in highly reduced graphene oxide and G-CaS. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanostructures; powder diffraction; Precipitation

Carbon allotropes: metal-complex chemistry, properties and applications - Sharma, Geeta (MRS Bulletin, 2020)

Correlation between multifunctional properties of lead free Iron doped BCT perovskite ceramics - Redhu, Preeti; Punia, Rajesh; Hooda, Ashima; Malik, B. P.; Sharma, Geeta; Sharma, Preeti (Ceramics International, 2020)
Present study investigates the effect of Fe doping on structural, microstructural, dielectric, ferroelectric, piezoelectric and magnetic properties of Barium calcium titanate (BCT) ceramics synthesized by solid state reaction route. The polycrystalline tetragonal structure of prepared ceramics was confirmed from XRD study. Analysis done using Rietveld refinement reveals reduction in lattice parameters as well as unit cell volume on substitution of Fe3+ ions in BCT lattice. Occurrence of four distinct Raman bands viz. 297 cm(-1) -302 cm(-1), 473 cm(-1)-475 cm(-1), 516 cm(-1) -524 cm(-1) and 729 cm(-1) -733 cm(-1) in Raman spectroscopic studies confirms the tetragonal phase of prepared ceramic compositions which are in accordance with XRD study. The Scanning Electron Microscopy analysis revealed polyhedral shaped grains whose average grain size decreased with increase in Fe content (x) in BCT ceramics. A diffused frequency independent phase transition was observed in temperature dependent dielectric measurements. Dielectric properties improved significantly, with shifting of transition temperature, T c close to room temperature with Fe doping. These studiessuggest applications of these ceramics in the development of environment friendly dielectric materials meeting X7R MLCCs specifications. The ferroelectric and piezoelectric properties of these ceramic compositions were found to decrease with increase in Fe concentration. Feeble room temperature ferromagnetism was observed for composition x = 0.020.
Keywords: BCT; dielectric response; Fe doping; ferroelectric properties; Lead free ceramics; Magnetic measurements

Role of charge compensation mechanism and defect dipoles on properties of Mn doped BCT ceramics - Redhu, Preeti; Sharma, Preeti; Hooda, Ashima; Singh, Anupinder; Sharma, Geeta; Punia, Rajesh (Ceramics International, 2021)
Single-phase Mn doped Barium Calcium Titanate (BCT) (Ba0.80Ca0.20Ti1-xMnxO3; x = 0.000, 0.005, 0.010, 0.015 and 0.020) lead free ceramics have been prepared by conventional solid-state reaction method. XRD studies and Rietveld refinement confirmed the existence of tetragonal phase (P4mm) for all prepared ceramic compositions. The average grain size increased up to x = 0.005 and thereafter it decreased with increase in Mn content in BCT compositions. Analysis of temperature-dependent dielectric study revealed phase transformation from tetragonal to cubic phase and defect dipole induced anomaly in paraelectric region of temperature-dependent dielectric constant ( epsilon'-T) curve. Degree of diffusiveness increased with Mn doping in BCT ceramics as confirmed by evaluating diffused phase transition (DPT) parameters (gamma and delta(c)) by Power Law fitting and width of diffused phase transition (D') obtained from derivative of epsilon'-T curve. Ferroelectric (P-E loops) study revealed that ceramic composition with x = 0.015 Mn content showed the highest remnant polarization (P-r) and maximum polarization (P-max) of 14.10 mu C/cm(2) and 24.20 mu C/cm(2) respectively. Enhancement in energy storage properties with applied electric fields have been observed at room temperature. Maximum energy storage density W-rec similar to 190.89 mJ/cm(3) with an efficiency of 48.63% has been obtained for x = 0.015. A large piezoelectric charge coefficient (d(33)) of 460 pC/N has been obtained for x = 0.020. The room temperature magnetic measurements shows feeble ferromagnetism for Mn doped samples. These studies suggest the application of these ceramics for multilayer ceramic capacitors, energy storage, and high power applications..
Keywords: Defect dipoles; Dielectric anomaly; Energy storage; Ferroelectric materials; ferromagnetic materials; Lead-free ceramics; Mn doped BCT; piezoelectric; Williamson-Hall (W-H)

Synthesis of graphene from activated carbon at liquid nitrogen temperature and its detailed structural analysis - Sharma, Preeti; Sharma, Geeta; Punia, Rajesh (Applied Physics A-Materials Science & Processing, 2021)
The present study deals with the synthesis of graphene using thermal quenching of pre-heated activated carbon (a-C) (1370 K for 3 h) at liquid nitrogen temperature and its detailed structural analysis using XRD, TEM, FTIR and Raman spectroscopy. The analysis of lattice parameters (L-a, L-c,L- and d) of constituent nanographitic domains using XRD shows restoration of graphene-like structure in the resultant product (a-CL). TEM image reveals porosity and partially crystallinity (from SAED) in a-C. While thin layers of graphene are observed in the TEM images of a-CL Deconvoluted Raman spectra have been used to investigate the evolution of crystalline behaviour of a-C with temperature in view of Ferrari and Robertson's three-stage model. The evolution of G peak and increase in I-D/I-G reveals restoration of crystallinity in a-CL. The development of the D peak indicates disordering of graphite but ordering of amorphous carbon. The reported method is technologically beneficial for graphene synthesis for large number of applications such as supercapacitors, H-2 storage, gas separation and purification.
Keywords: activated carbon; Amorphous carbon; graphene; H-2 storage applications; Raman spectroscopy; Supercapacitors

Luminescence turn-off detection of metal ions and explosives using graphene quantum dots - Jyotsna, Shubhra; Sadhu, Subha; Sharma, Vinay; Gupta, Preeti; Sharma, Geeta; Poddar, Pankaj (MRS Communications, 2022)
Green luminescent graphene quantum dots (GQDs) obtained from combustion of white printing paper were used for detection of fourteen different metal ions and six different explosives in an aqueous medium. These were obtained using a microwave-assisted synthesis process. After optimizing the experimental conditions (pH 6; quantum yield (QY) similar to 38.2%), a sensitive sensing system was developed to detect explosives and free residual metal ions in the environment based on fluorescence quenching of GQDs. The as-synthesized GQDs, as a sensing system, is most sensitive for Cu2+ ion and 2,4-DNP with a detection limit of 0.62 mu M and 0.50 mu M, respectively.